Data Modeling for Immunological and Clinical Data of Leukemia and Myasthenia Patients - Gerneth, F.; Haux, R.; Müller’, C. A. (Methods of Information in Medicine, 1992)
In this study it was investigated whether and to what extent semantic data models and their methods for data modeling are useful for adequate representation and integration of immunological and clinical data. To that end the special research program in leukemia research and immunogenetics (SFB 120) of the University of Tübingen was taken as an example. Based on the semantic data model RIWT we propose the design of a database system, report on its realization, and discuss this approach. Using a semantic data model, the quality of data increased considerably. This means, for instance, that the integration of the molecular-biological knowledge allows a better control of the person-related results. Hence, the decisions based of these data may have greater validity and the treatment on leukemia patients can be improved. Furthermore, the elucidation of immune mechanisms concerning auto-immune diseases could be improved.
Keywords: Database Design; Semantic Data Model; Hospital Information System; Immunology; Molecular Biology